1992
DOI: 10.1063/1.351619
|View full text |Cite
|
Sign up to set email alerts
|

Transmission studies of explosive vaporization of a transparent liquid film on an opaque solid surface induced by excimer-laser-pulsed irradiation

Abstract: The dynamics of the explosion of a liquid film by an ultraviolet excimer pulsed laser is studied experimentally on top of an amorphous silicon (aSi) film deposited on fused quartz. In particular, the transient temperature as well as the nucleation of the superheated liquid at the interface for laser fluences below and above the spontaneous nucleation threshold are monitored using an optical transmission technique. Results for different pure and mixed liquids are presented for cases of different thicknesses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Furthermore i t is observed that Ithe pressure wave generated by the liquid explosion causes repetitive cavitations at the surface of the solid sample. t -25 1.50 Time [wl [12]. The same argument holds also for the reflectance signal: decrease.…”
Section: Strictionsmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore i t is observed that Ithe pressure wave generated by the liquid explosion causes repetitive cavitations at the surface of the solid sample. t -25 1.50 Time [wl [12]. The same argument holds also for the reflectance signal: decrease.…”
Section: Strictionsmentioning
confidence: 52%
“…Due to the practical significance of this "s;team laser cleaning", many physical aspects such as nucleation dynamics, explosion tlmsholds for different Iiquids and substrates, and the pressures generated by the evaporation process need detailed investigation. Various methods including piezoelectric detection [ I I], optical transmission probe [12,13], and probe-beam deflection [I41 have been applied previously to the studies of these phenomena with some experimental re-…”
Section: Pacs: 6470fx 7920d~mentioning
confidence: 99%
“…'6"1 6 This method has been successfully applied to our studies on the nucleation dynamics of the explosive evaporation of liquid films on a-Si samples irradiated by UV laser pulses and provided useful data. 16,17 In a previous paper' 4 we pointed out that a larger temperature dependence of the optical constants for a-Si is possible in the stronger absorption regime. Therefore we extend here the investigations to shorter wavelengths, especially to the He-Ne laser wavelength.…”
mentioning
confidence: 92%
“…Initial studies had been performed on thin liquid films by using an optical transmission probe [14], which provides useful information on temperature transients and "explosion" thresholds. However, liquid film rupture and droplet formation in the path of the probe beam make data analysis difficult and, in addition, the optical transmission probe is limited to certain semitransparent solid substrates.…”
mentioning
confidence: 99%